Concepciones de cultura y de encuentros interculturales de futuros/as profesores/as de Alemán como Lengua Extranjera - Treder, Alexandra (Memorias del III Congreso Internacional de Lenguas, Lingüística y Traducción)

Implementing Digital Responsibility through Information Systems Research: A Delphi Study of Objectives, Activities, and Challenges in IS Research - Beverungen, Daniel; zur Heiden, Philipp; Lehrer, Christiane; Trier, Matthias; Bartelheimer, Christian; Bradt, Tobias; Distel, Bettina; Drews, Paul; Ehmke, Jan Fabian; Fill, Hans-Georg; Flath, Christoph M.; Fridgen, Gilbert; et al.

Potentials of a friction-induced recycling process to improve resource and energy efficiency in manufacturing technology - Borgert, Thomas; Milaege, Dennis; Schweizer, Swetlana; Homberg, Werner; Schaper, Mirko; Tröster, Thomas (International Journal of Material Forming)
Abstract Efforts to enhance sustainability in all areas of life are increasing worldwide. In the field of manufacturing technology, a wide variety of approaches are being used to improve both resource and energy efficiency. Efficiency as well as sustainability can be improved by creating a circular economy or through energy-efficient recycling processes. As part of the interdisciplinary research group "Light—Efficient—Mobile" investigations on the energy-efficient friction-induced recycling process have been carried out at the department of Forming and Machining Technology at Paderborn University. E.g. using the friction-induced recycling process, different formless solid aluminum materials can be direct recycled into semi-finished products in an energy-efficient manner. The results of investigations with regard to the influence of the geometrical shape and filling rate of the aluminum particles to be recycled as well as the rotational speed of the continuously rotating wheel are explained in this paper. In addition to the recycling of aluminum chips, aluminum particles like powders from the field of additive manufacturing are processed. Based on these results, the future potentials of solid-state recycling processes and their contribution to the circular economy are discussed. The main focus here is on future interdisciplinary research projects to achieve circularity in the manufacturing of user-individual semi-finished products as well as the possibility to selectively adjust the product properties with the continuous recycling process.
Keywords: General Materials Science

﻿DARC 2023 at Radboud University: Societal challenges in accounting research and education - De Meyst, Karen; Niederkofler, Thomas; Reimsbach, Daniel (Maandblad voor Accountancy en Bedrijfseconomie)
This year, the 7th edition of the Dutch Accounting Research Conference (DARC) was hosted by the Nijmegen School of Management at Radboud University on Thursday, March 23. In total, over 75 accounting researchers from various Dutch universities were welcomed by Frank Hartmann, chair of the accounting group and head of the Business Economics department. During the day, four keynote speakers presented their research and in a panel discussion, the current state of accounting education was debated. In the evening, participants gathered to network over dinner. This article presents a discussion of the theme of the conference, an outline of the research papers and projects presented during the conference, and a summary of the panel discussion on Accounting Education.
Keywords: General Arts and Humanities

Tax Complexity, Tax Department Structure, and Tax Risk - Giese, Henning; Koch, Reinald; Sureth-Sloane, Caren

Dietary flavonoids among children and adolescents in the Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study: intake, food sources and trends from 1985 until 2016 - Rienks, Johanna; Penczynski, Katharina J.; Schmitting, Sarah; Buyken, Anette; Nöthlings, Ute (British Journal of Nutrition)
Abstract Flavonoids are suggested to reduce disease risk. Since dietary habits are acquired during early life, describing age and time trends of flavonoid intake and major food sources are important for monitoring and disease prevention in later life. We aimed to describe total flavonoid intake and food sources and to investigate age and time trends of flavonoid intake in 3–18-year-olds, from the Dortmund Nutritional and Anthropometric Longitudinally Designed study from 1985 to 2016. Intake was assessed annually using 3-d weighed food records (WFR). Flavonoid values were assigned using the United States Department of Agriculture database. Foods contributing to intake were determined. Age and time trends in total flavonoid and isoflavone density were analysed by sex with PROC MIXED. In total, 1312 children completed 10 758 WFR. Across all ages, daily mean total flavonoid density was lower in boys compared with girls (134 v . 146 mg/4184 kJ) and no difference in median isoflavone density (0·04 mg/4184 kJ per d) was found. The top five foods contributing to total flavonoid intake were apple with peel (15·0/17·1 %), strawberries (5·9/6·1 %), chocolate spread (3·9/3·5 %), orange juice (3·5/3·4 %) and pasta (3·5/3·4 %) for boys and girls, respectively. Overall, in boys, total flavonoid density decreased over the course of age and time. In girls, there was no association with age or time. In both sexes, isoflavone density followed a U-shaped age trend with no change over time. From a public health perspective, the overall observed downwards trend of flavonoid intake in boys deserves attention. Future initiatives should be tailored at maintaining a high flavonoid density as children age, specifically among boys.

Business Intelligence & Analytics Cost Accounting: A Survey on the Perceptions of Stakeholders - Grytz, Raphael; Krohn-Grimberghe, Artus (Proceedings of the 51st Hawaii International Conference on System Sciences)
As data driven decision-making using business intelligence and analytics (BI&A) becomes standard in companies, the importance of mitigating the accompanying growth in costs increases. Research shows that increasing transparency to the granularity of individual BI&A artefacts such as reports or analytic applications is a necessary means, but in practice the introduction of said systems is cumbersome and adoption is slow. We address the status quo of BI&A cost accounting for three types of stakeholders: users, developers and managers. The results show in which areas of application a strong need for action exists and we identify major challenges for further research are ahead. Our findings indicate for example that managers at the same time regard cost accounting for BI&A with a higher potential benefit while they also believe they have already established a higher degree of implementation in their enterprises compared to the other stakeholder types. We conclude that BI&A professionals have to consider these different perceptions to run a successful department and gain traction for BI&A cost accounting.

A Summary of Survey Methodology Best Practices for Security and Privacy Researchers - Redmiles, Elissa M.; Acar, Yasemin; Fahl, Sascha; Mazurek, Michelle L.

Geschlechteridentitäten von Jugendlichen im Kontext von Social Media. Jahrestagung der Fachstelle Gender NRW (FUMA) am 26. Juni 2014 in der Volkshochschule Düsseldorf - Richter, Susanne (GENDER – Zeitschrift für Geschlecht, Kultur und Gesellschaft)
Zusammenfassung Auf der Tagung der Fachstelle Gender NRW (FUMA) „Geschlechteridentitäten von Jugendlichen im Kontext von Social Media“, die am 26.06.2014 in Düsseldorf stattfand, stand der Umgang mit neuen Medien im Mittelpunkt. Diskutiert wurden die Praktiken von Jugendlichen in sozialen Netzwerken und die Herausforderungen, die sich hieraus für Mitarbeitende der Kinder- und Jugendhilfe ergeben. Dabei wurde auch der Frage nach Auswirkungen auf Geschlecht und Geschlechtsidentitäten nachgegangen. Schlüsselwörter Internet, Neue Medien, Web 2.0, Pädagogik, Jugendarbeit, Geschlechtsidentität Summary Adolescent Gender Identities in the Context of Social Media. Annual conference of the specialist department Gender NRW (FUMA), Düsseldorf, 26 June 2014. The conference “Adolescent Gender Identities in the Context of Social Media” was held in Düsseldorf on 26 June 2014 and was hosted by the specialist department Gender NRW (FU-MA). It focused on the use of new media. Participants discussed adolescents’ practices in social networks and the resulting challenges for youth work professionals. The influence on gender and gender identity was also investigated. Keywords internet, new media, web 2.0, science of education, youth services, gender identity

The corporate marketing department - Between value and vanish - Ritter, T; Eggert, A; Münkhoff, E; Ulaga, W (ISBM 2014 Academic Conference)

On Hardy spaces of local and nonlocal operators - Bogdan, Krzysztof; Dyda, Bartłomiej; Luks, Tomasz (Hiroshima Mathematical Journal)

Application of Event Based Decision Tree and Ensemble of Data Driven Methods for Maintenance Action Recommendation - Kimotho, James Kuria; Sondermann-Wölke, Chritoph; Meyer, Tobias; Sextro, Walter (International Journal of Prognostics and Health Management)
This study presents the methods employed by a team from the department of Mechatronics and Dynamics at the University of Paderborn, Germany for the 2013 PHM data challenge. The focus of the challenge was on maintenance action recommendation for an industrial machinery based on remote monitoring and diagnosis. Since an ensemble of data driven methods has been considered as the state of the art approach in diagnosis and prognosis, the first approach was to evaluate the performance of an ensemble of data driven methods using the parametric data as input and problems (recommended maintenance action) as the output. Due to close correlation of parametric data of different problems, this approach produced high misclassification rate. Event-based decision trees were then constructed to identify problems associated with particular events. To distinguish between problems associated with events that appeared in multiple problems, support vector machine (SVM) with parameters optimally tuned using particle swarm optimization (PSO) was employed. Parametric data was used as the input to the SVM algorithm and majority voting was employed to determine the final decision for cases with multiple events. A total of 165 SVM models were constructed. This approach improved the overall score from 21 to 48. The method was further enhanced by employing an ensemble of three data driven methods, that is, SVM, random forests (RF) and bagged trees (BT), to build the event based models. With this approach, a score of 51 was obtained . The results demonstrate that the proposed event based method can be effective in maintenance action recommendation based on events codes and parametric data acquired remotely from an industrial equipment.
Keywords: maintenance decision; Bagged trees; Decision trees; PSO-SVM; Random forests

Gender, Diversity and a Competence Based Computer Science Curriculum - Weber, Jutta; Crutzen, Cecile (Festschrift for Christina Mörtberg)

Changes of users' discursive behavior in HRI - Lohse, Manja; Rohlfing, Katharina; Wrede, Britta (Presentation at the 10th International Pragmatics Conference (IPrA))
Whether interacting with a colleague from another department, a child with distinct cognitive and linguistic skills or a foreigner with different cultural background, humans try to adapt to their communication partners. The adaptation allows for a flow in communication and thereby for successful turn-taking. In contrast, when users communicate with artificial systems often reduced flow and turn-overtaking 4 are observable. The reasons for these insufficiencies may lie in the fact that little is known about the turn-taking strategies that dialogue systems should pursue 4. In our approach, we postulate that it is the feedback of the system and the interpretation of the feedback by the user that are in the center of an adaptation process As a result, one way to improve HRI, and especially its communicational flow, is to focus on different types of feedback and how they affect the user{’} discursive behavior. In contrast to former work concentrating on telephone based speech systems or multimodal systems consisting of a touch screen and speech 1, 2, 5, we study an embodied interaction with the service robot BIRON (BIelefeld RObot CompanioN). The general goal of the studies is to develop a situated system that can learn the spatial environment as well as the names and visual appearance of objects. Therefore, BIRON can not only understand spoken speech but also co-verbal deictic references to objects in the scene and carry out mixed-initiative dialogues. In our study, the subjects were asked to introduce objects to the robot by showing and pointing. This very restricted goal allowed us to compare verbal and gestural behavior across subjects. We analyzed the interactions of 15 native German speaking users communicating with BIRON. The interaction was carried out with the fully autonomous mode of BIRON, except for the speech recognition, which was simulated by keyboard input in order to avoid speech recognition errors. By using the autonomous interaction system, we were able to produce realistic communication sequences including problems caused by the complex interaction of the diverse perceptual system components. In analyzing the users{’} discursive behavior, we noticed different task-related interaction strategies. Focusing on subject{’}s consistency and changes of strategies in the course of the ongoing turn-taking, we analyzed which feedback of the system caused a change of a strategy within a user. We found that subjects decided for one strategy addressing one perceptual channel (vision or speech) of the system and used it as long as they did not receive any feedback about the failure of this specific channel. We observed a change in strategy when it became obvious to the subject via feedback that a particular perceptual channel was not working appropriately. The change in strategy was likely to maintain the interaction flow and thereby the user satisfaction. While these results support previous findings indicating when and how users change strategies 1, 5, they give new insights into the discursive behavior, i.e. into the repertoire of strategies in embodied and situated interaction. The results imply that within turn-taking, users interpret the system{’}s feedback and thus verify their model of the capabilities of the interlocutor. Thus, the change in discursive strategy is an indicator of users{’} expectation of how the robot functions 3. In further studies we plan to deliberately vary the robots misunderstandings and integrate the personality traits of the subjects into the research on strategies.

Unscharfe Produktionsprogrammplanung bei Alternativproduktion - Betz, Stefan

A honeypot for the exploration of spammers' behaviour - Schryen, Guido (IATAC IAnewsletter)

How Security Problems Can Compromise Remote Internet Voting Systems - Schryen, Guido (Workshop of the ESF TED Programme)
Remote Internet voting systems still suffer from many security problems which rely on the clients, the servers, and the network connections. Denial-ofservice attacks and viruses still belong to the most challenging security issues. Projects and studies like the ?Voting Technology Project? of CALTECH and MIT or SERVE of the US Department of Defense set up to gain experience evidence many of the notional weaknesses of current Internet voting systems.

Towards a Generic Model for AOP (GEMA) - Mehner, Katharina; Rashid, Awais

Extended Model Relations with Graphical Consistency Conditions - Hendrik Hausmann, Jan; Heckel, Reiko; Sauer, Stefan (Proceeding of the Workshop on Consistency Problems in UML-based Software Development (satellite event of the UML 2002), Dresden (Germany))
Consistency of models and model transformations are strongly interrelated topics. It is thus desirable to have a single notation to express model properties concerning both aspects. When using meta modeling techniques, graph transformations are a natural candidate to express model transformations. This paper explores the use of graph transformations for denoting consistency conditions between models. This technique yields benefits for different types of interrelation between transformation and consistency. A special focus is put on the generation of automatic consistency-establishing transformations.

On the Specification and Analysis of Protocols in UML-RT - Engels, Gregor; Küster, Jochen; Groenewegen, Luuk

On the Integration of Roles in the UML - Depke, Ralph; Engels, Gregor; Küster, Jochen

Modeling Agent-Based Systems with Graph Transformation - Depke, Ralph; Heckel, Reiko; Küster, Jochen

UML Collaboration Diagrams and Their Transformation to Java - Engels, Gregor; Hücking, Roland; Sauer, Stefan; Wagner, Annika

Graph Transformation for Specification and Programming - Andries, Marc; Engels, Gregor; Habel, Annegret; Hoffmann, Berthold; Kreowski, Hans-Jörg; Kuske, Sabine; Plump, Detlef; Schürr, Andy; Taentzer, Gabriele
The framework of graph transformation combines the potentials and advantages of both, graphs and rules, into a single computational paradigm. In this paper we survey recent developments in applying graph transformation as a rule-based framework for the specification and development of systems, languages, and tools. After presenting the basic features of graph transformation, we discuss a spectrum of applications including the evaluation of functional expressions, the specification of an interactive graphical tool, an example specification for abstract data types, and the definition of a visual database query language. The case studies indicate the need for a graph transformation language that provides suitable structuring principles and is independent of a particular graph transformation approach. To this end, we sketch the basic features of the new graph- and rule-centered language Grace, currently under development, that permits systematic and structured specification and programming based on graph transformation.

Operational Semantics of Algebraic Specifications with Conditional Equations - Pletat, Udo; Engels, Gregor; Ehrich, Hans-Dietrich